Georges Sorel's Study on Vico Translation, Edition, and Introduction - Brandom, Eric (Radboud Studies in Humanities, 2019)
This English translation of Sorel's Study on Vico opens the way to a radical re-evaluation not only of Sorel's trajectory, but of his French intellectual contexts, and the anarcho-syndicalism he is sometimes said to represent Readership: Students and researchers of fin de siècle European intellectual history; historians of the social sciences, and Marxism; students of Vico's legacy and of Sorel's social thought. Anyone interested in the roots of cultural studies.